2022
DOI: 10.3389/fmolb.2022.813637
|View full text |Cite
|
Sign up to set email alerts
|

Role of Globotriaosylceramide in Physiology and Pathology

Abstract: At first glance, the biological function of globoside (Gb) clusters appears to be that of glycosphingolipid (GSL) receptors for bacterial toxins that mediate host-pathogen interaction. Indeed, certain bacterial toxin families have been evolutionarily arranged so that they can enter eukaryotic cells through GSL receptors. A closer look reveals this molecular arrangement allocated on a variety of eukaryotic cell membranes, with its role revolving around physiological regulation and pathological processes. What m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 211 publications
(261 reference statements)
0
18
0
Order By: Relevance
“…We aimed herein to target Gb3 in tumours with genetically engineered T cells. Previous studies have demonstrated that Gb3 is overexpressed in leukaemia, colorectal, breast, lung, pancreatic, ovarian, and testicular cancer, among other malignancies [ 53 , 54 ]. Recently, enhanced expression of Gb3 has been described as correlating with the development of metastasis in colon cancer [ 33 , 42 ] and multi-drug resistance in breast [ 55 ], lung, ovarian [ 56 ] and myeloid leukaemias [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed herein to target Gb3 in tumours with genetically engineered T cells. Previous studies have demonstrated that Gb3 is overexpressed in leukaemia, colorectal, breast, lung, pancreatic, ovarian, and testicular cancer, among other malignancies [ 53 , 54 ]. Recently, enhanced expression of Gb3 has been described as correlating with the development of metastasis in colon cancer [ 33 , 42 ] and multi-drug resistance in breast [ 55 ], lung, ovarian [ 56 ] and myeloid leukaemias [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although tumour imaging studies in mice with StxB did not show extensive off-targeting [ 93 95 , 121 ], still there is a reasonable risk of targeting normal tissue in which Gb3 is also expressed, e.g. kidney [ 122 ], nervous system [ 123 ], liver or intestine [ 53 , 124 ]. The clinical translation of these findings remains to be done; our study is designed as a proof-of-concept, and it has herewith demonstrated the feasibility of targeting cancer cells by using novel and innovative lectin-CAR constructs.…”
Section: Discussionmentioning
confidence: 99%
“…We could also demonstrate that SaroL-1 is not active on Gb3- depleted cancer cells. As recently reviewed 67 , Gb3 is expressed in a limited number of human organs (lung, kidney, lymph node and CNS), so SaroL-1 might not be specific solely towards cancer cells, limiting possible applications in targeted treatments. Nonetheless, the Gb3-targeting verotoxin proved to be selective in the elimination of human tumor xenografts in mice 68 , 69 .…”
Section: Discussionmentioning
confidence: 99%
“…When bound to nonlipid raft Gb3, STxB follows the degradative pathway to lysosomes. , This fraction of lysosomal STxB offers an opportunity for the targeted intracellular delivery of drugs such as DBCO-PEG4-Val-Cit-PAB-MMAE. The delivery of antitumoral drugs by STxB was previously tested on Gb3-expressing tumor cell lines derived from colorectal, lung, or breast carcinomas. These human cell lines are an effective model for assessing the ability of STxB to deliver various treatments in vitro .…”
mentioning
confidence: 99%